Les Russes et les Italiens: un partenariat exemplaire - Yakemtchouk, Romain (Rivista di studi politici internazionali, 2011)
<!–[if gte mso 9]> Normal 0 14 false false false IT X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Tabella normale"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; –> <!–[endif]–> It were the Italian architects that allowed to introduce in Russia, in the XVIII century, the elements of European civilization which the tsars wanted to see in their country. After World War I, the Italian authoritarian regime was among the first to recognize the Soviet Union. After the collapse of communism, efforts to provide conditions for the fruitful development of political, economic and cultural cooperation between Russian Federation and Italy became one of the priorities in their activities: the number of joint ventures is steadily growing. The two governments reiterated their intention to increase the energy cooperation on long‐range level. Gazprom and Eni have inked an agreement on strategic partnership: Gazprom received the opportunity to launch direct Russian gas deliveries to the Italian market, and Eni is jointly engaged in the Blue Stream and in the South Stream gas pipelines. Italian Prime Minister Berlusconi and Russian Prime Minister Putin signed an agreement on nuclear energy: Enel Spa will build a nuclear power plant in the region of Kaliningrad. The Russian governement invited Italian businesses to help Russia in the nuclear, space, telecoms and pharmaceutical industries. Fiat will establish an important car factory in Tatarstan. The two partners are promoting step by step, peacefully and perseveringly, a solid and mutually advantageous Italo‐Russian cooperation. Ce sont les architectes italiens qui ont permis l’introduction en Russie, au XVIIIe siècle, des éléments de la civilisation européenne souhaitée par les tsars. L’Italie fut une des premières à reconnaître l’Urss dès 1924. Après la chute du fascisme, elle a établi des relations amicales avec les puissances et, tout en alignant sa politique étrangère sur l’Occident, s’efforça de réduire l’opposition entre l’Est et l’Ouest. Après l’effondrement du communisme, les autorités russes et italiennes ont tout fait pour accroître leur coopération et la rendre durable. Gazprom et Eni ont établi leur parténariat stratégique: l’entreprise russe fut autorisée à agir directement sur le marché italien, tandis que Eni s’engagea dans la construction et le financement des gazoducs Blue Stream et South Stream. Silvio Berlusconi et Vladimir Poutine ont signé un accord sur la coopération nucléaire: Enel érigera une centrale nucléaire dans la région de Kaliningrad. La Russie fit appel aux hommes d’affaires italiens pour soutenir le développement de ses industries nucléaire, spatiale, des télécoms et de la pharmaceutique. Fiat construira une nouvelle usine d’automobiles au Tatarstan. Les autorités des deux pays s’efforcent de promouvoir, pas à pas, pacifiquement et avec perséverance, une solide coopération russo‐italienne. MOTS‐CLES: Convergences culturelles; Coopération économique; Co‐entreprises; Silvio Berlusconi; Vladimir Poutine.